SOSIALISASI DAN PELATIHAN PEMBUATAN MIKROORGANISME LOKAL (MOL) BONGGOL PISANG SEBAGAI PUPUK ORGANIK CAIR DALAM MENDUKUNG PERTANIAN ORGANIK MASYARAKAT WAMENA, PAPUA INDONESIA - Inrianti; Patras Pumoko; Sepling Paling; Alber Tulak (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2022)
Abstract: Wamena is one of the areas with the potential to develop a wide variety of food crops and plantations in large and medium quantities because it is supported by its natural conditions. Wamena, especially throughout Jayawijaya Regency and even other Regencies in the Central Highlands of Papua, are known for their organic farming. In order to support and maintain the productivity of organic farming systems, as an academic activist in the agricultural sector, it is necessary to conduct training on making organic fertilizer through the use of banana weevils known as Local Microorganism Fertilizer (MoL). This training was based on observations of farmer groups in the Wesaput district, where all farmers in the farmer groups had never used organic liquid fertilizers or inorganic fertilizers as additional nutrients to increase the growth and production of their agricultural products. Therefore we try to provide understanding and approaches to farmer groups through community service on how to make Local Microorganism Liquid Fertilizer in order to increase the yields of local farmers in the Wesaput District, especially the village of Kama. As a result of this activity, we saw that the farmer group community in Wesaput gave a good response so they asked for similar activities to be carried out again so that the farmer group community was more independent in making and using liquid organic fertilizer using the natural resources around them.